Immunogenicity to Biotherapeutics – The Role of Anti-drug Immune Complexes - Krishna, Murli; Nadler, Steven G. (Frontiers in Immunology, 2016)
Abstract Biologic molecules are increasingly becoming a part of the therapeutics portfolio that has been either recently approved for marketing or those that are in the pipeline of several biotech and pharmaceutical companies. This is largely based on their ability to be highly specific relative to small molecules. However by virtue of being a large protein, and having a complex structure with structural variability arising from production using recombinant gene technology in cell lines, such therapeutics run the risk of being recognized as foreign by a host immune system. Given the range of immune mediated adverse effects that have been documented to biologic drugs thus far, including infusion reactions, and the evolving therapeutic platforms in the pipeline that engineer different functional modules in a biotherapeutic, it is critical to understand the interplay of the adaptive and innate immune responses, the pathophysiology of immunogenicity to biologic drugs in instances where there have been immune mediated adverse clinical sequelae and address technical approaches for their laboratory evaluation. The current paradigm in immunogenicity evaluation has a tiered approach to the detection and characterization of anti-drug antibodies (ADAs) elicited in vivo to a biotherapeutic; alongside with the structural, biophysical and molecular information of the therapeutic, these analytical assessments form the core of the immunogenicity risk assessment. However many of the immune mediated adverse effects attributed to ADAs require the formation of a drug/ADA immune complex intermediate (ICs) that can have a variety of downstream effects. This review will focus on the activation of potential immunopathological pathways arising as a consequence of circulating as well as cell surface bound drug bearing-ICs, risk factors that are either intrinsic to the therapeutic molecule or to the host which might predispose to IC mediated effects, and review the recent literature on prevalence and intensity of established examples of type II and III hypersensitivity reactions that follow the administration of a biotherapeutic. Additionally we propose methods for the study of immune parameters specific to the biology of ICs that could be of use in conjunction with the detection of ADAs in circulation.